Total Hip Arthroplasty - Case Report - Solano, Carla (2023)
Emergency departments receive patients with Total Hip Replacement or Total Hip Arthroplasty on a daily basis. One of the most common complications in the emergency department is hip/prosthesis dislocations, despite the low rate of postoperative complications. What individualises the case that we present is in the observation of the hip X-ray, with dislocation of the prosthesis, the singular location of the same. Two questions: Where was the prosthesis located in detail, post-dislocation; and how was it possible, according to the patient's information, to achieve some mobility with a walker or walking aid. Conclusion: throughout the process, radiology (conventional, computed tomography and radioscopic support) was fundamental to any outcome that the case might have.